Brand building and image perception in women football: a cross-country comparison between Brazil and Germany - Costa, A.; Secches Kogut, C. (Soccer & Society, 2024)
While women`s football (WF) experienced exponential growth after the 2019 FIFA Women`s World Cup, the drivers for building players` personal brands (PB) remain opaque to our understanding of the sport`s image. The purpose of this research is to provide a cross-country multidimensional comparison and multi-method exploration of this process based on self-presentation and gender roles. Thus, a mixed-method approach was adopted, encompassing: (1) a content analysis of Brazilian and German elite players` Instagram posts (n = 278); (2) in-depth interviews with national team players of both nationalities (n = 9); and (3) a survey with football fans of both countries (n = 430). The collective and embedded construction of a player`s PB as well as the global branding of WF are addressed in the discussion, contributing to the current debate surrounding athletes` brand construction in social media, from a multi-dimensional and comparative perspective.